A novel approach to fabricating a nanotwinned surface on a ternary nickel alloy. (15th September 2016) - Zhang, Zhenyu; Wang, Bo; Huang, Siling; Wen, Bin; Yang, Song; Zhang, Bi; Lin, Cheng-Te; Jiang, Nan; Jin, Zhongmin; Guo, Dongming
Abstract: Deformation nanotwinning is performed using molecular dynamics (MD) on a single crystal in a ternary nickel (Ni) alloy. Generalized embedded-atom method (EAM) potential functions are obtained for the ternary Ni alloy. The critical twinning stress is 4.48 GPa, calculated by the MD simulations. Detwinning, restoring and regenerating of nanotwins take place during the unloading process, contributing to the remaining of the ductility. According to the MD simulations, a novel approach is proposed to fabricating a nanotwinned surface using nanoindentation at room temperature. This is different from previous reports, in which high temperature, high pressure or chemical regents are employed. Graphical abstract: Highlights: A novel approach is proposed to fabricating a nanotwinned surface using nanoindentation at room temperature. Deformation nanotwinning is performed using molecular dynamics on a single crystal in a ternary nickel alloy. Nanotwins are confirmed in a ternary nickel alloy using high resolution transmission electron microscopy.